2021
DOI: 10.5194/tc-2020-372
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Surface composition of debris-covered glaciers across the Himalaya using spectral unmixing and multi-sensor imagery

Abstract: Abstract. The Hindu-Kush Himalaya mountain range is characterized by highly glacierized, complex, dynamic topography. The ablation area of these glaciers is often covered a highly heterogeneous debris cover mantle comprising ponds, steep and shallow slopes of various aspects, variable debris thickness and exposed ice cliffs. These surface elements are associated with differing ice ablation rates, and understanding the composition of the glacier surface is essential for a proper understanding of glacier hydrolo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…However, in high mountain areas, which experience frequent cloud activity and have a large amount of debris coverage, automatic and semi-automatic glacier mapping based on remote sensing images is challenging [1,11,20], and short-term studies such as these do not necessarily show stable changes over time. Debris-covered glaciers are a special type of glacier [21,22]. The surfaces of mountain glaciers are frequently covered in supraglacial debris, whose spectral characteristics are similar to those of rocks and soil at the foot of the mountain [21,23], making them hard to distinguish from rock glaciers and periglacial areas [24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in high mountain areas, which experience frequent cloud activity and have a large amount of debris coverage, automatic and semi-automatic glacier mapping based on remote sensing images is challenging [1,11,20], and short-term studies such as these do not necessarily show stable changes over time. Debris-covered glaciers are a special type of glacier [21,22]. The surfaces of mountain glaciers are frequently covered in supraglacial debris, whose spectral characteristics are similar to those of rocks and soil at the foot of the mountain [21,23], making them hard to distinguish from rock glaciers and periglacial areas [24].…”
Section: Introductionmentioning
confidence: 99%
“…Debris-covered glaciers are a special type of glacier [21,22]. The surfaces of mountain glaciers are frequently covered in supraglacial debris, whose spectral characteristics are similar to those of rocks and soil at the foot of the mountain [21,23], making them hard to distinguish from rock glaciers and periglacial areas [24]. Particularly in the Tibetan Plateau, owing to the influence of the monsoon climate, frequent cloud activity occurs during the glacier melting period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Khumbu region has been well studied in the last decades in terms of glacier mass balance using the traditional glaciologic method (Wagnon et al, 2013), the geodetic method (Bolch et al, 2008;Nuimura et al, 2012;Brun et al, 2017;Bolch et al, 2011;Rieg et al, 2018), energy balance models (Rounce and McKinney, 2014;Rounce et al, 2015;Kayastha et al, 2000), debris cover characteristics (Iwata et al, 1980;Watanabe et al, 1986;Nakawo et al, 1999;Iwata et al, 2000;Casey et al, 2011;Yukari et al, 2000), surface velocity (Quincey et al, 2009) and more recently mapping of supraglacial lakes and ice cliffs at glacier scale (Watson et al, 2016(Watson et al, , 2017a. Rates of change of the debris-covered glacier tongues in this area vary from −0.12 ± 0.05 % per year from 1962 to 2005 (Bolch et al, 2008) to −0.27 ± 0.06 % per year from 1962 to 2011 (Thakuri et al, 2014). Watson et al (2017a) reported a pond coverage area of 1 -7 % of the glacierized area for some glaciers in the Khumbu based on high resolution Pleiades data.…”
Section: Introductionmentioning
confidence: 99%